Equipping Students for a "Specific Uprising" Toward Justice: Lessons Learned from a University Prison Initiative. Issue 1 (1st January 2020) - Cioffi, Todd; Haggerty, Andrew F.; Bouman, Jeffrey P.
Abstract: Equipping students for citizenship has always been a core element of American higher education. Amid financial distress, changing technology, and global interconnectivity, the project of equipping citizens is becoming increasingly disembodied. Embracing the notion that one's physical place matters, one application of an embodied practice has been the development of educational programs inside prisons in the United States. Beginning in 2015, Calvin University launched one such program inside the Richard A. Handlon Correctional Facility called the Calvin Prison Initiative (CPI) with the goal of extending Calvin's mission to equip students to be "agents of renewal in the world." The program offers opportunity for individual renewal through personal development in the context of a rigorous curriculum that culminates in a bachelors degree, as well as communal renewal through the transformation of the culture within the prison animated by the CPI students therein. After a description of the program and its context, this article describes a pilot study which sought to understand the impact of the CPI on its participants, particularly on how they see themselves as moral and spiritual leaders within Michigan's prisons. Through analysis of 57 essay pairs—one when applying to the program, and one after a portion of the program was completed—the data suggest that CPI participants demonstrate growth in three key areas of personal, educational, and community formation. This article concludes with a discussion of implications for the program, future programmatic and research opportunities, and implications for embodied community engagement within Christian higher education writ large.